Type I IL-1 Receptor (IL-1RI) as Potential New Therapeutic Target for Bronchial Asthma. (5th July 2010) - Lee, Jyh-Hong; Wang, Li-Chieh; Yu, Hsin-Hui; Lin, Yu-Tsan; Yang, Yao-Hsu; Chiang, Bor-Luen
Abstract : The IL-1R/TLR family has been receiving considerable attention as potential regulators of inflammation through their ability to act as either activators or suppressors of inflammation. Asthma is a chronic inflammatory disease characterized by airway hyperresponsiveness, allergic inflammation, elevated serum total, allergen-specific IgE levels, and increased Th2 cytokine production. The discovery that the IL-1RI–IL-1 and ST2–IL-33 pathways are crucial for allergic inflammation has raised interest in these receptors as potential targets for developing new therapeutic strategies for bronchial asthma. This paper discusses the current use of neutralizing mAb or soluble receptor constructs to deplete cytokines, the use of neutralizing mAb or recombinant receptor antagonists to block cytokine receptors, and gene therapy from experimental studies in asthma. Targeting IL-1RI–IL-1 as well as ST2–IL-33 pathways may promise a disease-modifying approach in the future.